Editorial (Inglês) - Mota, Mauricio (REVISTA QUAESTIO IURIS, 2019)
The journal Quaestio Iuris, indexed in the Web of Science, of quarterly periodicity, in this volume 11, number 04, 2018, is pleased to inform all its readers that the article of the Magazine: ALBUQUERQUE, Isete Evangelista, THE RIGHT OF MINORITIES IN THE CONSTITUTION OF THE REPUBLIC OF BRAZIL AND THE SITUATION OF 1988 AS A MINORITY ETHNIC INDIANS OF THE BRAZILIAN STATE, published in the Journal Quaestio Iuris, Rio de Janeiro, no. 02, p. 11-32, 2013, was cited as a reference in the Study Guide II - GOMUN, of the COMMITTEE OF THE UNITED NATIONS GENERAL ASSEMBLY FOR SOCIAL, HUMANITARIAN AND CULTURAL AFFAIRS - SOCHUM. The UN General Assembly’s Committee on Social, Humanitarian and Cultural Affairs, also known as SOCHUM, is the third of six UN committees. The General Assembly emerged in 1945 in the final epoch of World War II with the aim of resolving issues that affect balance and peace. It is therefore the most important deliberative body in the world and has a total of 193 member countries. As the name implies, the aforementioned committee debates social, humanitarian and human rights issues of citizens around the world. In our Section Essays we published 05 (five) essays, being 02 (two) essays on public policies: Rationality, Predictability, Precedents and Public Administration and Legal effects of mineral tax policy at state of Pará: the illegality of tax deferral with tax exemption effects. In this issue of the Journal we kept our staff of our reviewers / evaluators, from countless states of the country and foreign professors, in a total of more than 650 (six hundred and fifty) evaluators. We also publish, for the immediate consultation of readers, the links of the various national and international indexes of journals where our Journal Quaestio Iuris is indexed. We thank, as always, all the readers, authors, evaluators and collaborators for the collaboration and trust and for the always excellent work done. We always remember that the submissions for the Journal Quaestio Iuris are permanent and must be performed by the system, directly on the Journal page. Good reading to all!